A Bibliometric Analysis of Publications on Endoscopic Ultrasound - Chen, Xiaoli; He, Huiqin; Chen, Xin; Chen, Xueqin; Wen, Zhenzhen; Xu, Mengque; Fang, Yanfei; He, Xingkang (Frontiers in Medicine, 2022)
Background: Over the past 40 years, endoscopic ultrasound (EUS) has become a safe and effective tool for both diagnostic and therapeutic applications. A growing number of articles have been published annually. We aimed to explore global scientific outputs and hotspots of EUS published by different countries, organizations, and authors. Methods: The global literature regarding EUS during the 1900-2020 period was identified from the Web of Science (WOS) Core database. “Bibliometrix” and software VOSviewer were applied to perform bibliometric analysis. Results: The annual growth rate of publications from 1980 to 2020 was around 16% and the number of EUS-related articles had experienced a sudden increase in the last decade. Bhutani MS was the most productive author over the past years, with 94 publications. Hawes RH had the highest number of citations , with 6034 citations. The United States and institutions from USA dominated the EUS research. Among the journals, GASTROINTESTINAL ENDOSCOPY published the highest number of articles, followed by ENDOSCOPY. The majority of top 10 frequently cited references were cited more than 200 times. Carcinoma, diagnosis, fine-needle-aspiration, cytology, and pancreatitis were the important keywords in co-occurrence analysis of keywords. Recent studies focused more on tissue acquisition, size of the needle, lumen-apposing metal stent, and fine-needle- biopsy. Conclusions: Research on EUS has significantly increased in the last decade globally and it will continue to increase . Active collaboration among different authors and countries was observed in the EUS field. Tissue acquisition, size of the needle, apposing metal stent, and fine-needle-biopsy might be the latest research frontiers and should receive more attention.